PSYCHOLOGICAL ASPECTS OF ADDICTION TO SOCIAL MEDIA, COMPUTER AND COMPUTER GAMES - Mukhamedova, Dilbar; Rakhimova, Indira; Nigmatullina, Liliya; Majidov, Nabijon; Abdullayev, Bobur (International Journal of Psychosocial Rehabilitation, 2020)
The rapid growth in the number and variety of technical devices affects many aspects of human life, the development of children in a space filled with various technical means affects the psychological characteristics of the personality of the child. In a few years, a generation that uses virtual space almost from birth will grow up. The constant use of social networks by adolescents affects the features of perception of information, interpersonal communication. This article discusses the theoretical foundations of the study of network dependence, the results of an empirical study on this topic.